2015
DOI: 10.1016/j.toxrep.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

One time nose-only inhalation of MWCNTs: Exploring the mechanism of toxicity by intermittent sacrifice in Wistar rats

Abstract: We have investigated the time-dependent effect of multi-walled carbon nanotubes (MWCNTs) in rats upon single inhalation exposure followed by intermittent sacrifice. The effects were monitored by analyzing the bronchoalveolar lavage fluid (BALF) and histopathological analysis. Cell count, neutrophils, lymphocytes, lactate dehydrogenase, alkaline phosphatase, protein and cytokines (tumor necrosis factor-alpha (TNF-α) and interleukin 4 (IL-4)) were significantly increased, while cell viability and alveolar macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Pulmonary exposure to multiwalled carbon nanotubes (MWCNTs) results in lung inflammation, pulmonary fibrosis, and lung adenocarcinoma promotion as well as extrapulmonary transport to many areas of the body [[9], [10], [11], [12], [13], [14], [15], [16]]. MWCNT-induced inflammation and extrapulmonary transport have numerous effects in vivo, including cardiovascular effects, increased oxidative stress, reduced cognitive abilities in rats, and disruption of the reproductive cycle in female mice [3,15,[17], [18], [19], [20]].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary exposure to multiwalled carbon nanotubes (MWCNTs) results in lung inflammation, pulmonary fibrosis, and lung adenocarcinoma promotion as well as extrapulmonary transport to many areas of the body [[9], [10], [11], [12], [13], [14], [15], [16]]. MWCNT-induced inflammation and extrapulmonary transport have numerous effects in vivo, including cardiovascular effects, increased oxidative stress, reduced cognitive abilities in rats, and disruption of the reproductive cycle in female mice [3,15,[17], [18], [19], [20]].…”
Section: Introductionmentioning
confidence: 99%
“…Further, a chronic inhalation study has linked MWCNTs (Mitsui 7s) with fibrosis in rodents (Fukushima et al, in preparation). Studies have shown that the potential for inhaled MWCNTs to induce fibrosis is influenced by their physicochemical properties (Ma-Hock et al 2009 ; Mishra et al 2012 ; Sargent et al 2014 ; Francis et al 2015 ). Fibrosis is therefore an important and relevant end point to consider for the risk assessment of MWCNT.…”
Section: Fibrosis Induction By Mwcnts: An End Point Relevant To Assesmentioning
confidence: 99%
“…The most widely used techniques for the synthesis of carbon nanotubes (CNTs) are laser furnace, chemical vapor deposition, and arc discharge [31]. Their biomedical applications include biosensors, orthopedic prostheses, anticancer therapy, and tissue engineering [32]. The literature reports reveal that maternal exposure of CNTs might develop developmental toxicity such as teratogenicity [33].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports reveal that maternal exposure of CNTs might develop developmental toxicity such as teratogenicity [33]. The threat of nanotoxicity of CNTs is an increasing trend, as the global production of CNTs reaches several thousand tons per year [32]. Based on morphology, the carbon nanotube is generally classified into the two viz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation